2009
DOI: 10.1179/102452909x451350
|View full text |Cite
|
Sign up to set email alerts
|

Actors' Interests and Local Contexts in Intrafirm Conflict: The 2004 GM and Opel Crisis

Abstract: Research on industrial relations in MNCs remains limited to aggregate concepts and dominant actor groups. Focusing on a case study of the 2004 wildcat strike at GM Bochum, Germany, this paper argues for the inclusion of genuinely local, micro-level perspectives and marginalised actors. It makes use of an extended framework of actor embeddedness, which introduces interests and situations as core variables. The case analysis shows how diverging interests of Opel shop stewards, workers and works council members l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Hence, subsidiary and headquarters actions need to be understood as the result of multi-actor political processes too. Blazejewski (2009), for instance, demonstrates in great detail how the interests of shop stewards, works council members, middle and top managers of a larger GM subsidiary in Germany strongly varied in intra-firm competition and how fiercely actors fought to influence subsidiary behaviour in intra-firm competition. Unfortunately, similar studies are not available for different types of actors in MNCs headquarters.…”
Section: Relevant Actorsmentioning
confidence: 99%
“…Hence, subsidiary and headquarters actions need to be understood as the result of multi-actor political processes too. Blazejewski (2009), for instance, demonstrates in great detail how the interests of shop stewards, works council members, middle and top managers of a larger GM subsidiary in Germany strongly varied in intra-firm competition and how fiercely actors fought to influence subsidiary behaviour in intra-firm competition. Unfortunately, similar studies are not available for different types of actors in MNCs headquarters.…”
Section: Relevant Actorsmentioning
confidence: 99%
“…Such differences, however, do not only originate from a national culture context but could also come from a variety of local communities, environments, or social classes. Importantly, while inhabitants of a nation state and the fields it comprises might partake in some of the same broader social and cultural dynamics, the interactions among employees within a firm are also shaped by their location in smaller fields, for example a local department or a social class (Blazejewski 2009). Consequently, studying the MNC in a practice perspective may shed light on how different individuals interpret and refer to the same nationalcultural contexts and values in quite diverse ways as they are guided by differential local interests 13 and concerns (Blazejewski 2009;Becker-Ritterspach and Dörrenbächer 2011).…”
Section: )mentioning
confidence: 99%
“…Hence a qualitative research revealed experience during the changes and showed a wider image of the relationship conflict between a manager and employees. This kind of perception may help improve conflict management, so that they do not turn into the general strikes as it happened at Opel and Kraft Food factories (Llorente et al, 2013;Blazejewski, 2009). …”
Section: Theoretical Framework Of the Researchmentioning
confidence: 99%
“…Analysis of research in this area reveals that power-based, rights-based, and interest-based conflict management systems have been created and tested (Roche and Teague, 2012). However, the use of conflict management, especially interest based conflict management is not wide-spread, the shortage of a constant approach means that many conflicts go unchecked resulting in strikes, stoppages, and undesirable consequences for employees and companies (Blazejewski, 2009; Llorente, Luchi and Sioli, 2013; Sondaitė and Norvilė, 2009; Sondaitė and Stunženaitė 2010). Irrespective of the fact of the use of a conflict management system, a personnel manager is held responsible for employee and employee-manager relations (Armstrong, 2014; SHRM Body of Competency and Knowledge, 2016).…”
Section: Introductionmentioning
confidence: 99%